CXCL12/SDF-1 in IgG4-Related Disease - Capecchi, Riccardo; Croia, Cristina; Puxeddu, Ilaria; Pratesi, Federico; Cacciato, Andrea; Campani, Daniela; Boggi, Ugo; Morelli, Luca; Tavoni, Antonio; Migliorini, Paola (Frontiers in Pharmacology, 2021)
Background: SDF-1/CXCL12 is a chemokine with pleiotropic functions in hematopoietic stem cell niche homeostasis, germinal center architecture, B cell maturation, neoangiogenesis, and fibrosis. Recently, the CXCL12/CXCR4/CXCR7 axis was associated with cancer metastasis and autoimmune diseases. The IgG4-related disease (IgG4-RD) is a pathological condition characterized by IgG4+ plasma cells infiltrating fibrotic lesions. The aim of this research is to investigate the relevance of SDF-1/CXCL12 in IgG4-RD. Materials and Methods: Peripheral blood samples were collected before therapy from a single-center cohort of 28 IgG4-RD patients, fulfilling the ACR-EULAR classification criteria. Clinical and serological data were obtained for each patient. In total, 14 healthy donors (NHS), 9 patients with pancreatic ductal adenocarcinoma (PDAC), and 9 with Sjogren syndrome (SSj) were recruited as controls and screened for circulating SDF-1/CXCL12 by ELISA. Moreover, paraffin-embedded pancreatic biopsies obtained from patients with IgG4-RD (n = 7), non-autoimmune pancreatitis (n = 3), PDAC (n = 5), and control tissues (n = 4) were analyzed to study the tissue expression and localization of SDF-1/CXCL12 and one of its receptors, CXCR4, and their potential relation with neutrophil extracellular traps (NETs). Results: IgG4-RD patients had higher serum levels of SDF-1/CXCL12 than normal controls (p = 0.0137). Cytokine levels did not differ between the IgG4-RD autoimmune pancreatitis (AIP) and retroperitoneal fibrosis nor between the single- and multiple-organ involvement. No correlation was seen with the IgG4-RD Responder Index, IgG4 levels, white blood cells, or inflammatory markers in the serum. When compared to SSj, the IgG4-RD AIP subgroup presents higher amounts of serum SDF-1/CXCL12 (p = 0.0275), while no differences are seen in comparison with PDAC. The expression of SDF-1/CXCL12 in the tissue was significantly higher in the IgG4-RD tissue than the normal pancreas, and the tissue with the high SDF-1/CXCL12 expression is characterized by the overall inflammatory cell infiltration, fibrosis, and high level of NETs. Conclusion: Modulating B cell development, neoangiogenesis and fibrosis, and SDF-1/CXCL12 may play a role in IgG4-RD. The higher levels observed in IgG4-RD, as compared to SSj, which closely mimics the disease, can be related to a different pattern of lesions, with prevalent fibrosis seen in IgG4-RD. Taken together, these findings suggest that drugs acting on the CXCL12/CXCR4/CXCR7 axis may affect IgG4-RD.